Pengaruh Kepemilikan Manajerial, Institusional, Asing dan Keluarga terhadap Kinerja Keuangan pada Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia 2014-2023 - Legina Steisi Pandensolang; Rochmad Bayu Utomo (Economic Reviews Journal, 2024)
In the midst of an increasingly competitive era of globalization, companies in the Indonesian consumer cyclicals sector are now facing significant challenges. A company's financial performance reflects its ability to manage financial resources effectively. Amid economic uncertainty, companies, especially those in the consumer cyclicals sector, often face many challenges related to financial stability and growth. This study examines the effect of managerial, institutional, foreign, and family ownership on financial performance. Based on Agency Theory, this study explores how ownership structure can affect managerial decisions and a company's financial results. The study focuses on the consumer cyclicals industry listed on the IDX from 2014 to 2023. Quantitative methods accompanied by statistical analysis are used in this study to test the effect of independent variables. Through purposive sampling, 16 companies were selected to be analyzed through multiple linear regression. The study findings show that family and managerial ownership have a positive impact on financial performance, while institutional and foreign ownership have a negative impact. In conclusion, ownership structure plays a significant positive role in influencing financial performance.